Gilbert's syndrome - bright and dark sides of the disease - literature review - Katarzyna Beutler; Jędrzej Lewandowski (Kazimierz Wielki University, 2024)
Gilbert's syndrome is the most common inherited jaundice worldwide. It affects 5-10% of the population. It is caused by a mutation of the UGT1A1 gene, which results in impaired bilirubin metabolism. It is a benign disease and does not affect the life expectancy of patients. Patients with Gilbert's syndrome should be alert to factors that exacerbate the course of the disease, interactions with medications taken and possible comorbidities such as hemolytic anemia, cholelithiasis or schizophrenia. However, it is the responsibility of physicians with such patients under their care to properly educate patients. Gilbert's syndrome carries not only the consequences associated with the mutation, but also has many benefits that patients may not be fully aware of. Mildly elevated bilirubin levels have an antioxidant and anti-inflammatory effect, which prevents the development of lifestyle diseases and cancer. Ongoing clinical trials suggest that this could be a great step toward new treatments for diseases affecting the entire human population.   PURPOSE OF THE WORK: This review paper aims to show Gilbert's syndrome as a multifaceted disease and to sensitize doctors' attention to patients with the described mutation.   MATERIALS AND METHODS: An analysis of papers available in PubMed and Google Scholar was performed using the following key words: Gilbert's syndrome, bilirubin, UDP-glucuronosyltransferase, Gilbert's syndrome harmful and protective aspects, iatrogenic Gilbert's syndrome   RESULTS: The result of the work is to present Gilbert's syndrome as a disease that carries medical problems directly related to the mutation, but also, in some cases, has a protective effect on affected individuals. The work highlights the complexity of the problem.